Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174058
|View full text |Cite
|
Sign up to set email alerts
|

Common Barriers to the Use of Patient-Generated Data Across Clinical Settings

Abstract: Patient-generated data, such as data from wearable fitness trackers and smartphone apps, are viewed as a valuable information source towards personalised healthcare. However, studies in specific clinical settings have revealed diverse barriers to their effective use. In this paper, we address the following question: are there barriers prevalent across distinct workflows in clinical settings to using patient-generated data? We conducted a twopart investigation: a literature review of studies identifying such ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 41 publications
3
63
0
Order By: Relevance
“…Providers are likely to need practice protocols to guide clinical responses to the data, visualizations, data reduction, or decision support to help make sense of the information while preventing overload, electronic health record (EHR) integration, and integration into clinical workflow. 3,12,13 Nationality studies, feasibility studies, and demonstration projects to integrate PGHD with EHRs are ongoing. 14,15 Prior to these national studies, in 2012, our academic multispecialty practice sought to facilitate the use of PGHD by enabling an electronic data tracking tool called a flowsheet.…”
mentioning
confidence: 99%
“…Providers are likely to need practice protocols to guide clinical responses to the data, visualizations, data reduction, or decision support to help make sense of the information while preventing overload, electronic health record (EHR) integration, and integration into clinical workflow. 3,12,13 Nationality studies, feasibility studies, and demonstration projects to integrate PGHD with EHRs are ongoing. 14,15 Prior to these national studies, in 2012, our academic multispecialty practice sought to facilitate the use of PGHD by enabling an electronic data tracking tool called a flowsheet.…”
mentioning
confidence: 99%
“…Some participants discussed that this reactive approach would extend to their use of self-monitoring technologies. This highlights how current models of self-tracking, which stress the importance of long-term consistent data points generated by the user [50], may not align with the symptom transience evident with CRCs. The notion of designing for symptom transience has been explored in HCI research around Parkinson's disease by McNaney et al [29] and Nunes and Fitzpatrick [11], describing the need for self-care tools to support variability in condition state.…”
Section: Designing For Reactive Managementmentioning
confidence: 97%
“…Similarly, Pols [40] found that daily peak flow readings were seen as counterproductive as they could only be interpreted in unhelpful ways, which did not improve the situation for the individual. This contrasts with the emphasis placed on ensuring patient generated data is being regularly collected to be useful for clinical care planning [50]. What can be deemed clinically relevant to a patient versus a healthcare professional can differ, as Pols [41] described how physiological readings can depict the condition of one's body in a way that may not be experienced directly by the patient themselves.…”
Section: Designing For Reactive Managementmentioning
confidence: 99%
“…In a clinical visit, self-tracking health data can be helpful for the physician especially when a patient has difficulties to express a clear reason for the visit [40]. West et al [49] confirm that patient-generated data promotes making decisions about further physical examination, but it is not alone sufficient for medical intervention partly due to its unknown accuracy. Current personal informatics tools available for personal data collection have variation in data accuracy, which sets requirements also for users to find personal strategies for making the data accountable [50].…”
Section: Introductionmentioning
confidence: 99%